Sanctions and Epitimia in the Orthodox Canonical Tradition - Maghioros, Nikos ca. 21. Jh. (Quaderni di diritto e politica ecclesiastica, 2019)
This paper aims to explain how the Orthodox Church deals with its disciplinary system and the way this system is regulated by the holy canons and the forms of its penitential procedure. The main idea is that a penance (ἐπιτίμιον) is considered to be neither a means of atoning for an unlawful action, nor a way of making compensation for damage or restoring the disturbed legal order. It is principally a procedure for curing any illness afflicting the soul as a result of sin. It is related to repentance (μετάνοια), the discernment (διάκρισις) of the spiritual physician (πνευματικός) and also the disposition (διάθεσις) or willingness (προαίρεσις) of the person who has sinned to follow the personalized cure. A penance is not a sanction of punishment (ποινή) but a procedure for overcoming the sinner’s fallen condition, the beginning of a process of spiritual transformation, re-edification and reconciliation, through the repentant person’s own free will. Gregory of Nyssa recapitulates the idea of this lawful and canonical procedure (ἔννομος και κανονική οἰκονομία), associating it theologically with the meaning of the feast of Pascha. The resurrection of the fallen man embraces his transformation by the grace of God through the washing of regeneration, as well as the repentance and conversion that leads again from dead works to the living way, to the saving hope.